KEPENTINGAN EKONOMI DAN POLITIK MEDIA DALAM RUANG PUBLIK INDONESIA - Meylda Adheista; Isma Nabilah; Muhammad Iqbal (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study aims to find out how the economic and political interests of the media in Indonesia are primarily related to public space in Indonesia. Especially in the 2019 presidential election wherein the capital owners controlled and even participated directly in political circles. The focus of this research is on the criticize of how the media can not be separated from political influence to achieve economic interests. The theory used in this research is the theory of political economy of media and the concept of public space. the paradigm used in this study is critical. The mass media, both print and broadcast (TV and Radio) play a very significant role in disseminating messages that are important to the public / society. Karl Marx states "that the mass media is referred to as the governing class, in the system of modern capitalism". political economy, becomes a gamble for the function and positioning of the media, whether they are able to carry out the function of the media as part of the press or are more likely to prioritize the business side, maybe even their political position.